Navigating The Obstacles and Complexities of ICT Integration in Pakistan's Education Sector - Uthman Shehu Lawal; Zohaib Hassan Sain (Al-Qalam Institute, 2024)
This research focuses on the main challenges and barriers to adopting information and communication technology (ICT) in educational institutions in Lahore, Pakistan. The research mainly focused on limited resources, outdated curriculum, and technophobia among educators. Using qualitative methods and a case study approach, the research collected data from various educational institutions through in-depth interviews, observations, and document analysis. A total of 15 interviewees, including teachers, school administrators, and technical staff, were purposively selected to provide deep insights into the issues studied. Data were analyzed using reduction, presentation, and verification techniques to identify key patterns. The results showed that resource limitations, such as lack of ICT devices and minimal budget, are the main barriers to technology integration. In addition, a curriculum that is irrelevant to the demands of the digital era slows the adoption of ICT in the learning process. Technophobia among teachers was also identified as a significant factor, with many educators feeling insecure about using technology due to a lack of relevant training and adequate technical support. The findings imply the need for a holistic strategy that includes providing adequate resources, curriculum reform, and continuous training for educators to support more effective technology integration. This research contributes significantly to understanding the challenges of ICT adoption in developing countries, particularly in Lahore. The results provide important insights for policymakers to design more inclusive and effective technology-based education policies while filling the literature gap in the context of ICT adoption in the education sector.